Malaria: A 10-year (1994-2003) retrospective study at University Malaya Medical Center (UMMC), Kuala Lumpur, Malaysia - Jamaiah, I.; Rohela, M.; Nissapatorn, V.; Khoo, B.L.; Khoo, P.S.; Radhiyah, M.; Aisyah, A. (2005)
Malaria is still one of the most important vector-borne diseases in Malaysia, particularly in remote areas. This retrospective study was carried out to find the prevalence of malaria among patients admitted to UMMC Kuala Lumpur, from 1994-2003. A total of 86 malaria cases were analyzed. Most cases occurred among foreigners 57% (49 cases) while Malaysians constituted 43% (37 cases). Among foreigners, Indonesians constituted the most 57% (28 cases). Among Malaysians, most cases occurred among the Chinese 35% (13 cases) followed by the Malays 30% (11 cases). Males 70%(60 cases) were more commonly affected. The majority of cases were within the 20-39 year age group (69%). Three species of malaria parasites were reported, of which Plasmodium vivax constituted the most 55%( 47 cases), followed by Plasmodium falciparum 29% (25 cases), and only four cases (5%) of Plasmodium malariae. Nine percent (8 cases) were mixed infections. In this study, 12%(10 cases) developed chloroquine resistance: 7 cases of P. falciparum, and 3 cases of P. vivax. The most common complications were jaundice and anemia 77% (23 cases), followed by blackwater fever 13% (4 cases) and cerebral malaria 10% (3 cases). Most of the complications were due to P. falciparum 43% (13 cases). There were no reported deaths. This new source of malaria coming from foreigners must be given serious attention, as it has great potential of increasing malaria cases in urban Malaysia.